Konsep Arsitektur Berkelanjutan pada Desain Sekolah Alam di Polewali Mandar - Alfiansyah, Muhammad; Alfiah, Alfiah; Abdullah, Sudarman (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2024)
Natural schools are one of the alternative education models developing in Indonesia, different from the conventional education system. This approach aims to help students grow into individuals who have good morals. In contrast to conventional schools which tend to focus on learning in the classroom, natural schools encourage students to learn more outdoors by utilizing learning strategies that are fun and action-oriented. Through this direct learning approach, students at natural schools become more enthusiastic and enthusiastic in the learning process, which makes them less likely to get bored. The aim of this paper is to design a Natural School by utilizing the concept of sustainable architecture, with a focus on lighting, air circulation, and the use of environmentally friendly materials in building design. The research method used is a qualitative method, which aims to describe the potential for sustainable natural school development from an environmentally friendly perspective. The discussion process begins with data collection, which is then analyzed and synthesized to form a design concept. Data collection was carried out through qualitative descriptive methods. The results of this design include the implementation of sustainable architectural concepts with a focus on lighting efficiency and the use of environmentally friendly materials in the school building.